Point-contact-spectroscopy investigation of the Kondo size effect in CuCr and AuFe alloys - Fisun, V.V.; Yanson, I.K.; Mydosh, J.A.; van Ruitenbeek, J.M. (Физика низких температур, 2000)
Size effects in Kondo scattering are studied on CuCr and AuFe alloys (TK=2 K and 0.2 K, respectively) by applying point-contact spectroscopy in break-junction type contacts. It is shown that as the contact diameter is decreased under the condition of ballistic electron transport, the size effect enhances the interaction of the conduction electrons with the Kondo impurity (as compared to the phonons) and increases the Kondo temperature in the contact region. In an external magnetic field the size effect decreases the negative magnetoresistance in CuCr and suppresses the Kondo peak splitting in AuFe.